Understanding diversion programmes as an intervention for women with mental health issues: A realist review - Charlotte Brady; Rochelle A. Burgess; David Osrin (Elsevier, 2022)
Purpose: Women in prisons are known to suffer with mental health difficulties and many experience challenges prior to incarceration. Diversion programmes are initiatives designed to divert people with pre-existing mental illness from the criminal justice system into mental health services. The variability of effectiveness of interventions makes realist approaches particularly appropriate for diversion programmes, and this paper presents the first realist review to be undertaken across the breadth of this topic. This realist review aimed to explain the successes, failures and partial successes of these programmes as an intervention to improve the outcomes of women offenders with mental health issues. Methods: We conducted a realist review of published literature explaining the impact of diversion programmes on participants with mental health issues. Consultations with six specialists in the field were conducted to validate the principles and hypotheses about key dynamics for effective programmes. Results: The review included 69 articles. We identified four essential principles, developed through thematic groupings of context-mechanism-outcome configurations, to articulate key drivers of the effectiveness of diversion programmes: coordination between services; development and maintenance of relationships; addressing major risk factors; and stabilisation through diversion programmes. Conclusions: The behaviour of women offenders is driven by need, and the complex needs of this group require individualised plans that incorporate relationships as vehicles for support and change. Although there is a role for gender-specific interventions, it is not fully understood and further research is required. Implications for future interventions are discussed.